KESIAPAN GURU SEKOLAH DASAR DALAM PELAKSANAAN PEMBELAJARAN TEMATIK INTEGRATIF PADA KURIKULUM 2013 - Anna Astiningtyas (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2018)
This study aims to implement the readiness of teachers in integrative thematic teaching facing the 2013 curriculum. The background of the importance of the readiness of elementary school teachers in facing the 2013 curriculum is by implementing integrative thematic learning in the learning process. The data collected involves 10 research journals to compare teacher preparedness outcomes and the data can be analyzed using percent results. The results show that theoretically the teacher already has an understanding of the curriculum 2013, but still lacking in the implementation. Actually the motivation of teachers in implementing instructional innovation is very high, unfortunately it is less supported than facilities, facilities and infrastructure. Readiness of teachers in implementing the 2013 curriculum is included in the high category. Teachers have high expectations for the implementation of the 2013 curriculum to have a positive impact on the quality of learning. This study uses document studies from the results of previous studies. Data collection is done by searching for the Google Scholarly electronics journal. From the search results obtained, each model selected 10 journals for further analysis in percent (%) form. From the results of the analysis of the readiness of elementary teachers in the implementation of integrative thematic learning can be seen from the lowest 4.2% to the highest 35% with an average of 17.3%.